Writing Techniques for Classroom Activities - María Emilia Acosta; Sonia Riveros (Asociación Colombiana de Profesores de Ingles, 2016)
Writing is not just putting something down on paper. It is part of a process when learning a foreign language. "Learning to communicate with other people: to understand them, talk to them, read what they have written and write to them" (Raimes, 3). In this process the cognitive skills are involved. When writing the intellectual effort is great. It is to put in practice what has been learned in theory.